SOYBEAN SEEDLING ROOT GROWTH PROMOTION BY 1-AMINOCYCLOPROPANE-1-CARBOXYLATE DEAMINASE-PRODUCING PSEUDOMONADS - Edi Husen; Aris Tri Wahyudi; Antonius Suwanto; Rasti Saraswati (Indonesian Agency for Agricultural Research and Development, 2009)
Pseudomonad producing 1-aminocyclopropane-1-carboxylate (ACC) deaminase (E.C.4.1.99.4) has been known to promote plant growth by lowering ethylene biosynthesis in higher plants, which can be induced by indole-3-acetic acid (IAA) production. The objective of this study was to examine the ability of IAAproducing Pseudomonas isolated from local soil environment (rhizosphere of soybean grown in Plumbon's agricultural areain Cirebon, West Java, Indonesia) to promote soybean root growth in relation to their ACC deaminase activities. The experiments were conducted in growth room and Laboratory of Soil Biology Research, Indonesian Soil Research Institute, Bogor, from January to August 2008. Soybean seeds were inoculated by immersing the seeds for 1 hour in bacterial cell suspension containing approximately 108-109 cells ml-1. The seeds were then germinatedfor 2 days before planting in growth pouches containing sterilized distilled water. All treated and untreated seeds were grown for 7 days in growth room at 24°C with 1300 lux of light intensity for 12-hour followed by a 12-hour dark period at 22°C. ACC deaminase activity of the isolates was assayed based on their ability to grow in Dworkin-Foster’s salt minimal medium containing ammonium sulfate or ACC as a source of nitrogen. Thirteen out of 81 isolates tested significantly increased soybean root length and weight, up to 50% from untreated plants. Of 13 isolates, 11 demonstrated ACC deaminase activities. Two isolates that did not show ACC deaminase activities had lower capacity to produce IAA. The results suggest that the effectiveness of IAA producing Pseudomonas in promoting the growth of the soybean seedlings is associated with their ACC deaminase activities or they produce IAA at low levels.